Development Of Child Beginning Reading Ability Through Snake And Ladder Game - Kasmiati Kasmiati; Sinta MIftakhul Janah; Heru Kurniawan (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2023)
In Indonesia, reading activities are still being debated, because early childhood learn while playing or playing while learning or with something fun so that if young children are taught to read, they will become depressed because the child is not ready to accept. Therefore, so that learning can be done in a fun way, it is necessary to have game tools to support children's learning activities so that they become more creative using a modified snakes and ladders game. This research uses a descriptive research type which is used to obtain data in the form of both written and spoken text. Collecting data in this study using observation techniques, interviews and documentation. The analysis technique used is the analysis of the Miles and Huberman models which consist of three activities, namely reduction, data presentation and drawing conclusions. The results showed that using snakes and ladders games can develop early reading skills in early childhood, especially children aged four to five years, and show a sense of enthusiasm in learning and enthusiastic about following it to completion.